First report of paralytic shellfish poisoning (PSP) caused by Alexandrium tamiyavanichii in Kuantan Port, Pahang, East Coast of Malaysia - Mohammad Noor, Normawaty; Adam, Aimimuliani; Lim, Po Teen; Leaw, Chui Pin; Lau, Winnie; Liow, Guat R.; Muhamad Bunnori, Noraslinda; Hamdan, Nurul Ashima; Md Nor, Azlan; Kemat, Norazizah; Muniadi, Devaraj (Wiley-Blackwell, 2018)
Harmful algal bloom (HAB) is a proliferation of algae, which naturally produce biotoxins and cause harmful effects to humans, the environment and organisms associated with it. Paralytic shellfish poisoning (PSP) was reported for the first time in Kuantan Port, Pahang, Malaysia, in November 2013, followed by a second episode in August 2014. The toxicity level reported during the second event was as high as 3500 μg of STX equiv./100 g shellfish. Ten people were hospitalized with PSP symptoms after consuming contaminated shellfish. This study was conducted at Kuantan Port to identify the organisms responsible for these events. Water samples were collected monthly for a period of 12 months beginning in September 2014. HAB species were identified based on their morphology using light and fluorescence microscopes, and their classification was supported by molecular evidence based on internal transcribed spacer (ITS) sequences. Monthly cell abundance of Alexandrium tamiyavanichii was measured at four sampling stations. Toxin production by three strains isolated from the area was determined using HPLC. Our results revealed the presence of several HAB species, including the PSP-producing species A. tamiyavanichii. The highest cell density of A. tamiyavanichii was 840 cells L−1 . The presence of GTX components was detected in these strains. However, other toxin components could not be determined.This study reported, for the first time, the presence of PSP-producing A. tamiyavanichii on the Pahang coast of east Peninsular Malaysia and confirmed that the PSP events in Kuantan Port were attributable to this species. The presence of this species further indicates that several safety measures need to be considered to safeguard public health, particularly in Pahang coastal waters